Design and fabrication of MnO2 @ZIF-8 composite for electrochemical sensing of environment pollutant hydrogen peroxide - Ahmad, Khursheed; Raza, Waseem; Alsulmi, Ali; Kim, Haekyoung (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2023)
Hydrogen peroxide (H2O2) is widely used in various industries and food processing. Despite various applications, H2O2 possess negative effects on human being and aquatic life. Thus, determination of H2O2 is necessary to avoid its negative impacts. Electrochemical sensing approach has received enormous interest due to its simple processing, sensitivity, cost-effectiveness, and selectivity. Herein, we reported the fabrication of manganese dioxide (MnO2) on to a zeolitic imidazolate framework-8 (ZIF-8). Further, as-synthesized MnO2@ZIF-8 was characterized by various advanced characterization approaches (powder X-ray diffraction, scanning electron microscopy, energy dispersive X-ray and X-ray photoelectron spectroscopy). Furthermore, H2O2 sensor was developed by surface modification of glassy carbon electrode (GCE) with as-prepared MnO2@ZIF. The sensing activity of MnO2@ZIF-8/GCE was investigated by employing cyclic voltammetry (CV) and linear sweep voltammetry (LSV) techniques. A decent sensitivity of 0.856 µA.µM−1.cm2, detection limit of 0.157 µM and linear dynamic range of 10–100 µM were achieved for the determination of H2O2.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Electrochemical sensor; Hydrogen peroxide; MnO; ZIF-8